Computer Vision to Enhance Behavioral Research on Insects. (23rd January 2019) - Manoukis, Nicholas C; Collier, Travis C
Abstract: New or improved technologies can enable entomologists to address previously intractable questions, especially in the area of insect behavior. In this review, we describe the basic elements of applied computer vision for entomologists: image capture, data extraction, and analysis. We describe some of the currently available options in imaging hardware and cameras, lighting, software, as well as some basic data collection scenarios, and give detailed examples from our own experience. We suggest that the study of insect behavior is increasingly based on quantification of behavioral phenomena, that use of computer vision techniques for quantification will increase, and that the application of these tools and approaches will bring new insight and answers to questions in entomology. We hope this review can serve as a starting point for those interested in delving deeper into how computer vision can be applied to their research.